Social media integration: An opportunity for SMEs sustainability - Emmanuel Bruce; Solomon Keelson; John Amoah; Sulemana Bankuoru Egala (Cogent Business & Management)
The changing trend in the circular economy has pushed most firms to be competitive in their business activities using emerging technology. SMEs in recent times are increasingly leveraging technologies such as social media to enhance their interactions with their customers, increase their reach and become competitive. Despite this, SMEs in the manufacturing sector in developing economies are often underexplored in literature in their resolve to leverage social media to improve their performance and sustainability. This research explores the integration of social media in SME manufacturing firms’ activities toward their performance and sustainability in developing countries. Drawing on relevant literature and the social media engagement theory, we employed a questionnaire survey to collect data from 417 managers/staff of SME manufacturing firms in Ghana, using PLS-SEM techniques for the analysis. Research findings revealed that social media integration proved a direct positive correlation with SME manufacturing firms’ performance. Additionally, it was revealed that social media utilization has a positive and significant effect on SME manufacturing firms’ performance. The findings further show that social media usage assists SME firms’ performance and fosters their sustainability. It is concluded that SMEs should incorporate social media marketing strategies for firms’-customer relationships and internal and external collaboration. By implication, this study offers practitioners and researchers knowledge regarding social media integration among SMEs in emerging economies.